Gestion des ressources humaines et santé au travail : science de l’action ou de la réaction ? - Claire Edey Gamassou; Grégor Bouville; Tarik Chakor; Stéphan Pezé; Virginie Moisson (Perspectives Interdisciplinaires sur le Travail et la Santé)
Although Human Resources Management (HRM) examines the issue of people at work and their management from the angle of how best to serve an organization's performance, occupational health issues are still a blind spot in its research. Following the lead of Chakor, Abord de Chatillon, and Bachelard (20152) in their review of occupational health and safety research, we attempted to find out how scientific managerial approaches are constructed and how researchers in HRM position themselves with regard to occupational health. A sizeable corpus of texts - which were selected from three sources that were identified as representative of the management sub-discipline that is HRM - were subjected to both thematic content and descriptive statistical analyzes. We demonstrated the gradual empowerment of HRM researchers by building a managerial corpus for workplace health and we identified the salient features that characterize occupational health research in HRM in terms of research objects, methodologies, interdisciplinarity, and stances. This article concludes with a proposed research agenda for HRM scholars working on occupational health.